Reconstituting the constitution - Morris, Caroline 1973-.; Boston, Jonathan 1957-.; Butler, Petra, |d 1966-.; SpringerLink (Online Service). (Berlin, Heidelberg Springer Berlin Heidelberg Imprint: Springer, 2011)
In this volume, scholars, practitioners, politicians, public officials, and young people explore these questions and others in relation to the New Zealand constitution and provide some thought-provoking answers. This book is recommended for anyone seeking insight into how a former British colony with bicultural foundations is making the transition to a multicultural society in an increasingly complex and globalized world.
Part 1: Reconstituting the Constitution: An Overview--Part 2: Reforming Constitutions: Lessons from Abroad--Part 3: The Republican Question--Part 4: The Need for a Written Constitution? Strengthening the Bill of Rights Act and the Place of the Treaty of Waitangi--Part 5: The Future of Electoral Law--Part 6: Australia: Involving Civil Society in Constitutional Reform--Part 7: Influence of International Treaties--Part 8: The Trans-Tasman Relationship--Part 9: The Role and Governance of Sub-National Government--Part 10: Protecting Future Generations--Appendix.
Electronic reproduction.
Keywords: Constitutional law -- New Zealand -- Congresses; Constitutional law -- Congresses; Electronic books